The Implementation Of It-Based Learning Media At The State High School In Sidoarjo, East Java: Implementasi Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi (TIK) di Sekolah Menengah Atas Negeri (SMAN) di Sidoarjo, Jawa Timur - Taufiq, Wahyu; Yunanto, Angga; Affandi, Aditya Krisna; Pamungkasari, Silvana Desy (Procedia of Social Sciences and Humanities, 2024)
The study was done in a state senior high school in Sidoarjo, East Java. The tactics employed include observation and interviews. Researchers studied school culture, school management, and learning implementation in state high schools in Sidoarjo, East Java, as they used IT-based learning. Data from observations and interviews were evaluated to provide a full understanding of the school's teaching and learning processes. This study will watch and examine the teaching and learning process in state senior high schools in Sidoarjo, East Java. According to the findings of this study, the use of IT-based learning media in school is facilitated by the usage of laptops and projectors, the GDB Online application, and the E-Learning platform (Moodle). The findings indicate that technology makes learning engaging, efficient, and interactive. It is intended that this research will help to better understand school culture and management, as well as learning in the classroom.